Evaluation of Cooperative Learning to Increase Student Motivation at Mts Nurul Ali Secang - Fina Umu Rif Athi; Zulpan Syarif Supriadi Hasibuan; Otisia Arinindyah; Nur Saidah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Cooperative learning (Cooperative Learning) is education that focuses on organizing students into small groups to collaborate in order to improve the learning environment and achieve learning goals. This learning paradigm is often used to implement student-centered teaching and learning activities, especially to overcome the challenges that instructors have when trying to engage children who are hostile, unable to interact with others, or who do not care about others. The aim of this research is none other than to find out the evaluation of cooperative learning to increase the learning motivation of MTs Nurul Ali Secang students. The method used in this research uses qualitative research methods, using three data collection methods. First, observation, interviews, third, documentation. The results of this research show that there are three evaluations used by MTs Nurul Ali Secang teachers in evaluating cooperative learning to increase motivation for their learning. First, observe student participation, second, hold formative exams, and listen to feedback from students. Third, carry out regular reflections on the effectiveness of cooperative learning in achieving learning goals. Then the method he uses is four things. The first is group formation, the second is the division of roles, the third is continuous improvement, the fourth is collaboration with fellow teachers.